Provision of Maintenance for Former Wives of Civil Servants According to Government Regulation No. 45 of 1990 - Lingga, Anggi Salsha Musdalifa; Sembiring, Idha Apriliana; Barus , Utary Maharany (Jurnal Hukum Indonesia, 2025)
Government Regulation of the Republic of Indonesia Number 45 of 1990, civil servants who have divorced are obliged to provide maintenance to the former wife after the divorce. The primary purpose of this research is to analyze the provisions for providing maintenance to former civil servant wives in Government Regulation number 45 of 1990 and KHI, to find out the responsibility of a civil servant husband when a divorce occurs according to Indonesian positive law, to find out the analysis of legal decisions on the provision of maintenance for former civil servant wives according to Government Regulation Number 45 of 1990 in decision 27/Pdt.G/2022/PA.Tte. The method used in this study is normative juridical research using secondary data taken from primary, secondary, and tertiary legal materials. The results of this study explain that there are several factors for providing maintenance to former civil servant wives, according to PP 45 of 1990. Providing maintenance to the ex-wife of a civil servant has good legal consequences for the position of a wife and civil servant. Regarding legal considerations, the judge in Decision Number 27/Pdt.G/2022/Pa.Tte has been based on and by Indonesian favorable legal regulations.